Genome-wide identification and dynamic transcriptome profiling of the DYW-type PPR family across greening of chlorotic leaves in pear (Pyrus pyrifolia) - Lu, Liqing; Zhang, Haiqi; Zha, Zixian; Wang, Xueqian; Ma, Na; Liu, Chunyan; Xu, Yiliu; Gao, Zhenghui; Qi, Yongjie (Frontiers in Plant Science, 2026)
IntroductionPear (Pyrus pyrifolia) chlorotic leaves severely impair photosynthesis and the accumulation of photosynthetic products, primarily due to abnormal chloroplast development. DYW-type PPR proteins play a crucial role in regulating chloroplast development and maintaining structural integrity.MethodsTo comprehensively characterize the involvement of DYW-type PPR proteins in pear leaf and chloroplast development, we performed a genome-wide identification of 129 DYW-type PPR proteins in pears and systematically analyzed their sequence diversity, protein domain architecture, and evolutionary relationships.ResultsCompared with the wild-type ‘Chuxialv’, the ‘Chuxialv’ bud mutant exhibits reduced chlorophyll and ferrous ion content, along with disrupted chloroplast ultrastructure in leaves. Using this paired material, we conducted high-depth whole-genome resequencing to identify structural variations within the DYW-type PPR gene family. Furthermore, RNA-seq was performed on leaf samples from yellow to green, spanning five distinct developmental stages to construct a temporal expression profile of DYW-type PPR genes. Six DYW-type PPR genes exhibiting differential expression were identified, and protein-protein interaction network analysis of them, coupled with functional enrichment analysis, provided the underlying regulatory mechanism in chloroplast development and photosynthesis. Coexpression and functional regulatory networks of DYW-type PPR genes were constructed by integrating weighted gene co-expression network analysis with gene ontology enrichment analysis. Notably, only the coexpression module centered on PpPPR115 was enriched in photosynthesis-related biological processes. Furthermore, the MYB transcription factor binding motif was identified in the promoter region of PpPPR115. Six MYB transcription factors down-regulated in the CM1 compared with CL1 were excavated. Dual-luciferase reporter assays and yeast one-hybrid assays confirmed that PpMYB102 may act as a key upstream regulator of PpPPR115.DiscussionIn conclusion, this study elucidated the structural variations and dynamic expression patterns of the DYW-type PPR gene associated with chlorotic leaves in pears, offering novel insights and potential regulatory pathways relevant to chloroplast development and the transformation of chlorotic leaves to green in pears.